Efektivitas Program Optimalisasi Pajak Bumi dan Bangunan Perdesaan Perkotaan dalam Pencapaian Target Pajak Desa Temu Kabupaten Sidoarjo - A, A’isah; Pradana, Galih Wahyu; Ma’ruf, Muhammad Farid; Fitrie, Revienda Anita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Rural and Urban Land and Building Tax (PBB-P2) Optimization Program is one of the local government’s efforts to increase tax revenue and support regional development. However, its implementation still faces several challenges, particularly regarding the accuracy of tax targeting and collection. This study aims to analyze the implementation of the PBB-P2 Optimization Program in Temu Village, Prambon District, Sidoarjo Regency, focusing on the accuracy of tax object and subject data, the role of the Tax Assessment Compilation List (DHKP), and its impact on tax revenue realization. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. Research informants included village government officials, tax officers, and taxpayers. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the PBB-P2 Optimization Program in Temu Village has been implemented in accordance with applicable regulations. However, inaccuracies in tax targeting persist due to the lack of optimal updating and validation of tax object and subject data. Issues such as unseparated tax objects, untransferred ownership names, and unrecorded physical changes of land and buildings contribute to high levels of PBB-P2 arrears. The utilization of DHKP data and spatial mapping reveals that tax arrears are widely distributed and structural in nature. In conclusion, the optimization of PBB-P2 is not solely dependent on normative target setting but requires strengthened field-based data collection, continuous administrative validation, and the integration of information technology to improve targeting accuracy and tax collection effectiveness.